Chromosomal microarray in prenatal diagnosis: case studies and clinical challenges. (May 2016) - Leavitt, Karla; Goldwaser, Tamar; Bhat, Gifty; Kalia, Isha; Klugman, Susan D; Dolan, Siobhan M
Chromosomal microarray analysis (CMA) is a diagnostic tool used in the evaluation of pediatric patients with congenital anomalies or developmental and intellectual disability. In both the pediatric and prenatal patient population, CMA has been shown to have a higher detection rate of chromosomal abnormalities than conventional karyotype alone. Currently, the diagnostic yield of prenatal CMA is highest when applied to the evaluation of a fetus with multiple ultrasound anomalies. Challenges arise when CMA yields isolated findings not associated with a phenotype on ultrasound or variants of uncertain significance, which warrants evaluation of the risks, benefits, limitations and optimal incorporation of CMA into prenatal care. The clinical cases presented here will be used to illustrate these issues.